ANALISIS PENERAPAN TEORI OBJEKTIVITAS DALAM ASURANASI KAPAL ANTARA PT. BRINGIN SEJAHTERA ARTAMAKMUR DAN PT. DJAKARTA LLOYD (STUDI PUTUSAN NO.423/PDT.G/2011/ PN.JKT.PST.) - Gibran Budi Nugroho; Stanislaus Atalim (Jurnal Hukum Adigama, 2018)
In the insurance agreement, of course, there is an insurance object where the insurance object must be notified in detail by the insured to the insurer if it will not be threatened by the cancellation of the agreement. This is supported by one of the theories developed in insurance business, namely the theory of objectivity supported by article 251 KUHD This research is a study of the application of the theory of objectivity to Decree Number 423 / Pdt.G / 2011 / PN.Jkt.Pst because of the claim from PT. Djakarta Lloyd from the insurance object in the form of MV Jatiwangi PB 400 vessel that has been insured to PT Asuransi Bringin Sejahtra Artamakmur (PT BSAM), but the insurance company rejects the claim on the grounds that the ship was damaged at the time of signing the insurance policy. So that the problem arises how to apply the theory of objectivity to the rejection of insurance claims made by (PT BSAM)? is the application of the theory of objectivity in Indonesian insurance law correct? The research method used is a normative juridical research method. Data from the study shows that based on Article 251 KUHD and the theory of objectivity is a description of the honesty of insurance participants with the threat of cancellation of insurance if the insured party is proven not to have good intentions. Based on the definition of objectivity theory and Article 251 KUHD the author wants to discuss how it applies to ship insurance